Control of Omni-Directional Mobile Robot Motion - Al-Ammri, A. Salam; Ahmed, Iman (Al-Khwarizmi Engineering Journal, 2010)
This paper presents the motion programming and control of omni-directional mobile robot through the process of building and programming a small robotic platform with secondary design criteria of modularity and simplified control. This is accomplished by combining the positive aspects of several different robotics platform ideas. The platform is shaped like an equilateral triangle with a servo motor, sensors, and omni-wheel, controlled by a PIC microcontroller. In this work the kinematics, inverse kinematics and dynamic module for the platform is derived. Two search algorithms (the wall-following search and the “most-open-area” search) is designed, tested, and analyzed experimentally.